Peningkatan Kemampuan Pengetahuan IPA Pada Materi Siklus Air Hujan Menggunakan Model PBL Dikelas V SDN Cijoho - Lia Yulistiani Lia; Aiman Faiz; Rohadi (Jurnal Lensa Pendas, 2023)
The traditional teaching method, which is dominated by lectures and teacher explanations, often fails to generate students' interest and motivation. Additionally, students are less involved in experimental activities, and the learning process is not connected to real-life phenomena, resulting in suboptimal learning outcomes. This research aims to investigate the use of the problem-based learning (PBL) approach to enhance students' scientific knowledge, specifically focusing on the water cycle topic in fifth-grade classrooms. By implementing the problem-based learning approach, it is expected that students will become more active and engaged in the learning process and develop a better understanding of the water cycle. The research will be conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. Quantitative data analysis will be used to analyze the data based on students' learning outcomes throughout the learning process. Based on the results of the classroom action research, it was found that implementing the problem-based learning model can improve learning outcomes. The improvement in students' abilities was determined based on the percentage of evaluation scores. In the first cycle, it was observed that the learning outcomes were not achieved, with 16 out of 25 students scoring below 75%, representing 64%. Meanwhile, nine students achieved a score of 75% or above, accounting for 36%. In the second cycle, it was found that all 25 students achieved satisfactory learning outcomes, with a score of 75% or above, representing 100%.Keyword : Learning Model, PBL, Water Cycle.